ANALISIS KEBUTUHAN PELATIHAN PUSTAKAWAN BERBASIS KOMPETENSI INTI DI INSTITUT PERTANIAN BOGOR (Core Competence-based Training Need Analysis for Librarian in Bogor Agricultural University) - R.A. Abdul Qodir S.; Pudji Muljono; M Joko Affandi (Perpustakaan IPB, 2017)
AbstractThe core competence of the librarian is the functional competence that each librarian has in carrying out the library task. Increased professional competence of librarians can be done through training appropriate to the needs of librarians using Training Needs Assessment (TNA). TNA is capable of producing objective, systematic, and sustainable training needs. The purpose of this study was to analyze the core competency level of core librarians, establish training needs and priorities of training, and provide recommendations for training programs. The research was conducted by survey and interview method. A total of 16 librarians atthe Bogor Agricultural Institute because respondents use questionnaires with self-evaluation techniques. The results show there are some actual professional competencies that are under ideal competence. The priority of training programs is the information literacy and internet network for library services. The recommended methods used are on the job training and off the job training. Recommended as a training method to improve the core competence of librarians.Keywords: compentency, higher education, librarian, TNA-T, training need assessment.